Our common future - World Commission on Environment and Development (Oxford Oxford University Press, 1987)
In 1983, the U.N. General Assembly created the World Commission on Environment and Development, an independent committee of twenty-two members, headed by Gro Harlem Brundtland, the Prime Minister of Norway. Designed to examine global environment and development to the year 2000 and beyond, the commission seeks to reassess critical problems, to formulate realistic proposals for solving them, and to raise the level of understanding and commitment to the issues of environment and development.
Includes bibliographies
Keywords: Sustainable development